Dural arteriovenous fistulae after cerebral venous thrombosis - Ferro, José M.; Coutinho, Jonathan M.; Jansen, Olav; Bendszus, Martin; Dentali, Francesco; Kobayashi, Adam; van der Veen, Bas; Miede, Corinna; Caria, Jorge; Huisman, Holger; Diener, Hans-Christoph (Stroke, 2020)
Background and Purpose:This analysis examined the frequency of dural arteriovenous fistulae (dAVF) after cerebral venous thrombosis (CVT) in patients included in a randomized controlled trial comparing dabigatran etexilate with dose-adjusted warfarin (RE-SPECT CVT [A Clinical Trial Comparing Efficacy and Safety of Dabigatran Etexilate With Warfarin in Patients With Cerebral Venous and Dural Sinus Thrombosis]), who had systematic follow-up magnetic resonance (MR) imaging.Methods:RE-SPECT CVT was a Phase 3, prospective, randomized, parallel-group, open-label, multicenter, exploratory trial with blinded end point adjudication. We allocated patients with acute CVT to dabigatran 150 mg twice daily or dose-adjusted warfarin, for 24 weeks and obtained a standardized MR protocol including time-of-flight MR angiography, 3-dimensional phase-contrast venography, and 3-dimensional contrast-enhanced MR venography at the end of the treatment period. A blinded adjudication committee assessed the presence of dAVF in a predefined substudy of the trial.Results:We analyzed development of dAVF in 112 of 120 randomized patients; 57 allocated to dabigatran and 55 to warfarin. For 3 (2.7%) of these 112 patients, quality of follow-up imaging was insufficient to evaluate dAVF. A dAVF (Borden I) was found in 1 patient (0.9%) allocated to warfarin; however, this dAVF was already present at baseline. The patient did not present with hemorrhage at baseline or during the trial and was asymptomatic at follow-up.Conclusions:Despite systematic imaging, we found no new dAVF 6 months after CVT. Routine follow-up cerebral MR angiography aiming to detect new dAVF 6 months after CVT has a very low yield.Registration:URL: https://www.clinicaltrials.gov. Unique identifier: NCT02913326.